Reintegration of Karachi port through sustainable adaptive reuse of abandoned and underused industrial buildings - Naveed Iqbal; Syed Hamid Akbar; Koenraad Van Cleempoel (Acta Polytechnica CTU Proceedings)
The economic capital and one of Pakistan’s most important cities gain popularity due to the reputable Karachi port. Karachi was referred to as Korokala and Debal in ancient times; a city conquered by famous conquerors, including Alexander the Great and Muhammad bin Qasim due to its seaport importance. However, most of the port’s tangible and material heritage were built by the British during the 19th–20th century. The Britishers conquered the city and started developing Karachi port because of the seaport. Due to the port, the area of Karachi grew from a small fishermen’s village to a bustling metropolitan city. During the second industrial revolution in the late 19th century, the Britishers developed Indian industries so that they depended on British capital goods. To transport the goods, the British empire constructed railways and maritime routes in the mid and late nineteenth century, The port of Karachi was one of them. Karachi port remains the hub of Pakistan’s main logistic transportation, but some of its heritage buildings have been neglected on this site. After the 9/11 tragedy in the US, due to security reasons, Karachi port trust restricted the port to the public. Now, the security situation is better, and the port can be reintegrated and made accessible to the public through sustainable adaptive reuse of abandoned or underused buildings. Karachi is a congested city with few places for recreation; reintegrating this site can open opportunities for tourism while showcasing the city’s industrial heritage. This paper wants to articulate the potential of industrial heritage. But the latter in Pakistan is not yet recognized as part of a heritage discourse. The port offers a rich case study due to its layered history and various typologies of buildings on site.